Analisis Hukum Perjudian Togel di Wilayah Hukum Polres Indramayu: Perspektif Hukum Positif - Sukenda, Sukenda (Strata Law Review, 2024)
Efforts to combat gambling crimes can be carried out in practice through preemptive measures, widespread public awareness campaigns, preventive actions (before the occurrence of any gambling crime), and repressive actions to enforce the law against individuals engaged in gambling activities. These three prevention efforts are interdependent and form an inseparable chain in combating criminal activities in general, including specifically Togel gambling crimes.  How does the Indramayu Police Resort undertake efforts to prevent Togel gambling crimes from a positive legal perspective? In this research, the author employs a normative method. In legal studies, the normative method refers to an approach that focuses on determining what "should be" law or legal policy based on moral criteria or widely recognized values. Law enforcement efforts to prevent and eradicate gambling crimes, especially Togel gambling, are necessary to prevent its proliferation and maintain social harmony. Law enforcement is the process of implementing legal desires for society to obey and is an obligation to do so. The goal of law enforcement is to enhance societal order and legal certainty. This is achieved by regulating institutions tasked with enforcement according to their respective scopes and through effective cooperation contributing to goal achievement.